Integrated geophysical investigation of the Karoo Basin, South Africa - Scheiber-Enslin, Stephanie E (My University, 2016)
The possibility of extensive shale gas resources in the main Karoo Basin has resulted in a renewed focus on the basin, and particularly the Whitehill Formation. The main Karoo Basin has been the subject of geological studies since before the 1920s, but geophysical data provides an opportunity to shed new light on the basin architecture and formation. In this thesis, I use regional gravity, magnetic and borehole data over the basin, as well as vintage seismic data in the southern part of the basin. Modern computational capacity allows for more information to be extracted from these seismic data, and for these data to be better integrated with potential field data. The integration of datasets in a three-dimensional model (3D) has allowed for a better understanding of the shape of the basin and its internal structure, in turn shedding light on basin formation. A new depth map of the basin constructed using this extensive database confirms that the basin deepens from on- to off-craton. The basin is deepest along the northern boundary of the Cape Fold Belt (CFB), with a depth of ~4000 m in the southwestern Karoo and ~5000 m in the southeastern part of the basin. Sediment thickness ranges from ~5500 to 6000 m. The Whitehill Formation along this boundary reaches a depth of ~ 3000 m in the southwest and ~4000 m in the southeast. Despite limited boreholes in this region, the basin appears to broadly deepen to the southeast. These seismic and borehole data also allow for mapping of the Cape Supergroup pinch-out below the Karoo basin (32.6°S for the Bokkeveld and 32.4°S for the Table Mountain Group), with the basin reaching a thickness of around 4 km just north of the CFB. The gravity effect of these sediments in the south is not sufficient to account for the low of the Cape Isostatic Anomaly near Willowmore and Steytlerville. This ~45 mGal Bouguer gravity low dominates the central region of the southern Karoo at the northern border of the CFB. The seismic data for the first time show uplift of lower-density shales of the Ecca Group (1800 – 2650 kg/m3) in this region, and structural and seismic data suggest that these lower density sediments continue to depth of 11 to 12 km along normal and thrust faults in this region. Two-dimensional density models show that these shallow crustal features, as well as deeper lower crust compared to surrounding regions, account for the anomaly. These seismic and borehole data also allow for constraints to be placed on the distribution and geometry of the dolerite intrusions that intruded the basin after its formation, and in some cases impacted on the shale layer, to be constrained. The highest concentrations of dolerites are found in the northwest and east of the basin, pointing towards two magma sources. The region of lowest concentration is in the south-central part of the basin. Here the intrusions are confined to the Beaufort Group, ~1000 m shallower than the shale reservoir, suggesting it should be the focus of exploration efforts. These dolerite sills are shown to be between 5 and 30 km wide and are saucer-shaped with ~ 800 m vertical extent, and dips of between 2° and 8° on the edges. The sheets in the south of the basin extend for over 150 km, dipping at between 3° and 13°, and are imaged down to ~ 5 km. This change in dip of the sheets is linked to deformation within the Cape Fold Belt, with greater dips closer to the belt, although these sheets do not appear to intrude strata dipping at more than 15 to 20°. In order to understand the shape of the Karoo basin and construct a 3D model of the basin, an understanding is needed of the underlying basement rocks. The Beattie Magnetic Anomaly (BMA) that stretches across the entire southern part of the basin forms part of the basement Namaqua-Natal Belt. Filtered magnetic data confirm that the Namaqua and Natal Belts are two separate regions with different magnetic characteristics, which is taken into account during modelling. The BMA is shown to be part of a group of linear magnetic anomalies making up the Natal Belt. The anomaly itself will therefore not have an individual effect on basin formation, and the effect of the Natal Belt as a whole will have to be investigated. An in-depth study of outcrops associated with one of these linear magnetic anomalies on the east coast of South Africa suggest the BMA can be attributed to regions of highly magnetic (10 to 100 x 10-3 SI) supracrustal rocks in Proterozoic shear zones. Along two-dimensional magnetic models in the southwestern Karoo constrained by seismic data, these magnetic zones are modelled as dipping slabs with horizontal extents of ~20-60 km and vertical extents of ~10-15 km. Body densities range from 2800- 2940 kg/m3 and magnetic susceptibilities from 10 to 100 x 10-3 SI. These, as well as other geophysical and geological constraints, are used to construct a 3D model of the basin down to 300 km. Relatively well-constrained crustal structure allows for inversion modelling of lithospheric mantle densities using GOCE satellite gravity data, with results in-line with xenolith data. These results confirm the existence of lower density mantle below the craton (~3270 kg/m3) that could contribute to the buoyancy of the craton, and an almost 50 kg/m3 density increase in the lithospheric mantle below the surrounding Proterozoic belts. It is this change in lithospheric density along with changes in Moho depths that isostatically compensate a large portion of South Africa’s high topography (<1200 m). The topography higher than 1200 m along the edge of the plateau, along the Great Escarpment, are shown to be accommodated by an asthenospheric buoyancy anomaly with a density contrast of around 40 kg/m3, while still mimicking the Bouguer gravity field. These findings are in line with recent tomographic studies below Africa suggesting an “African Superplume” or “Large Low Velocity Seismic Province” in the deep mantle. The basin sediment thickness maps were further used to investigate the formation of the main Karoo Basin. This was accomplished by studying the past flexure of the Whitehill Formation using north-south two-dimensional (2D) profiles. Deepening of the formation from ~3000 m in the southwest to ~4000 m in the southeast is explained using the concept of isostasy, i.e., an infinite elastic beam that is subjected to an increasing load size across the Cape Fold Belt. Load height values increase from 4 km in the southwest to 8 km in the southeast. This larger load is attributed here to “locking” along a subduction zone further to the south. The effective elastic thickness (Te) of the beam also increases from around 50 km over the Namaqua and Natal Belts in the southwest to 80 km over the Kaapvaal Craton and Natal Belt in the southeast. The changes in Te values do not correlate with changes in terrane, i.e., a north to south change, as previously though. The large extent and shape of the Karoo basin can therefore, in general, be explained as a flexural basin, with the strength of the basement increasing towards the southeast. Therefore, while factors such as mantle flow could have contributed towards basin formation, reducing the load size needed, it is no longer necessary in order to account for the large extent of the basin. This flexure model breaks down further to the southeast, most likely due to a very high Te value. This could be the reason for later plate break in this region during Gondwana breakup. It is inferred that this increase in Te is linked to the buoyancy anomaly in the asthenospheric mantle.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, August 2015 School of Geosciences, University of the Witwatersrand
Keywords: Geophysical investigations -- South Africa -- Karoo Basin.; Basins (Geology) -- South Africa -- Karoo.